Relationship of Parities with Benefits Knowledge of Maternal and Child (KIA) Book for Pregnant Women at Public Heath Centre 1 Gamping 1 - Belian Anugrah Estri (International Journal of Health Science and Technology, 2020)
Public awareness about pregnant women health’s still a determining factor for MMR and IMR. Although there are still many factors that must be considered to deal with this problem, one of the causes of death is the ignorance of pregnant women and their families in recognizing danger signs of pregnancy, to solve this the government is trying to improve awareness and knowledge of pregnant women and their families with maternal and child health books (KIA). This study aims to to determine whether there is a relationship between parity and knowledge about the benefits of the KIA Handbook for pregnant women at Gamping 1 health center. This research is a quantitative study. The data collection method based on the time approach used is the cross section method. The sampling technique used was purposive sampling, namely taking samples according to the inclusion and exclusion criteria of 45 respondents with the Chi Square relationship test with a significance level of 95%. Chi Squere test results show that the p-value is 0.020. Therefore, the p-value α (0.05) means that there is a relationship between parity and the knowledge of pregnant women on the KIA Handbook at the Gamping 1 Health Center in Yogyakarta. Pregnant women are expected to continue to use and read the KIA Handbook during pregnancy in order to increase mother's knowledge.